An Unusual Presentation of Zollinger-Ellison Syndrome - Sinagra, Emanuele (S. Karger AG, 2013)
Zollinger-Ellison syndrome is an often progressive, persistent and frequently life-threatening disease, described for the first time as characterized by ulceration of the upper jejunum, hypersecretion of gastric acid and non-beta islet cell tumors of the pancreas; this syndrome is due to the hypersecretion of gastrin. We report a case of Zollinger-Ellison syndrome presenting as severe esophagitis evolving in stenosis, which demonstrates how a delayed diagnosis may induce risk of disease spreading. In this setting new diagnostic approaches, such as somatostatin receptor scanning and positron emission tomography with 68 Ga-labeled octreotide, could be particularly useful, as well as further new therapeutic options, such as molecular targeted treatments and peptide receptor radionuclide therapy, though surgery is currently the only form of curative treatment, and the role of the therapeutic options mentioned needs to be clarified by forthcoming studies.